Faktor – Faktor yang Mempengaruhi Niat Kewirausahaan di Provinsi Jawa Tengah dan di Provinsi Jawa Barat Hasil GEM 2022 - Fiona Stella Pricilia; Gandhi Pawitan (ATRABIS Jurnal Administrasi Bisnis (e-Journal), 2024)
In 2024, Indonesia is experiencing economic instability. This can be seen by the rampant layoffs (Termination of Employment) on a mass basis. There is a jump of 46,000 jobs that have lost their jobs (Ashhadi, 2024). From this problem, an alternative solution is obtained, namely by opening jobs or it can also be by increasing knowledge about entrepreneurship. This research will examine the variables of independent creativity, self-efficacy, business networks/networks, and the introduction of opportunities for the dependent variables, namely entrepreneurial intentions in Central Java Province and West Java Province. This study uses binary logistics regression analysis using SPSS application. The results of this study are that the creativity variable has a significance value of 0.402 > 0.05 (alpha), H1 is rejected so that the creativity variable does not have a significant influence on entrepreneurial intention; the self-efficacy variable has a significance value of 0.053 < 0.1 (alpha), H2 is accepted meaning that self-efficacy has a positive influence on entrepreneurial intentions; the business opportunity variable has a significance value of 0.181 > 0.05 (alpha), H3 the business opportunity variable has no influence on entrepreneurial intentions; the business network/network variable has a significance value of 0 < 0.05 (alpha), H4 is accepted means that the business network/network has a positive influence on entrepreneurial intention; The regional variable has a significant value of 0.824 > 0.05 (alpha), H5 is accepted meaning that the region has no influence on entrepreneurial intention. It can be concluded that self-efficacy and business networks/networks have a significant positive influence on entrepreneurial intentions. Keywords: Creativity, Self-efficacy, Business opportunity, Business Network, Entrepreneurial Intentions.